2023
DOI: 10.1111/jpy.13308
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct glycoconjugate cell surface structures make the pelagic diatom Thalassiosira rotula an attractive habitat for bacteria

Abstract: Interactions between marine diatoms and bacteria have been studied for decades. However, the visualization of physical interactions between these diatoms and their colonizers is still limited. To enhance our understanding of these specific interactions, a new Thalassiosira rotula isolate from the North Sea (strain 8673) was characterized by scanning electron microscopy and confocal laser scanning microscopy (CLSM) after staining with fluorescently labeled lectins targeting specific glycoconjugates. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 82 publications
(180 reference statements)
1
12
0
Order By: Relevance
“…This strain was isolated from T. rotula and presumably is a member of the bacterial core community of this diatom (Amin et al, 2015;Mönnich et al, 2020). Previous observations showed that this strain adheres to tuft-like structures of this diatom, which are visible only by CLSM after staining with fluorescent lectins, and/or forms aggregates (Tran et al, 2023). Our findings are in line with these observations but our microscopic inspection did not detect the tuft-like structures visible by CLSM.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This strain was isolated from T. rotula and presumably is a member of the bacterial core community of this diatom (Amin et al, 2015;Mönnich et al, 2020). Previous observations showed that this strain adheres to tuft-like structures of this diatom, which are visible only by CLSM after staining with fluorescent lectins, and/or forms aggregates (Tran et al, 2023). Our findings are in line with these observations but our microscopic inspection did not detect the tuft-like structures visible by CLSM.…”
Section: Discussionsupporting
confidence: 91%
“…However, physical interactions and colonization patterns of these bacteria and algae and aggregates have been studied only little. It has been shown that Roseobacteraceae and Flavobacteriales colonize distinct surface structures of diatom cells and aggregates (Bennke et al, 2013; Grossart, 1999; Tran et al, 2023). However, it is still unknown whether distinct bacterial taxa dwelling in association with algae preferentially colonize algal cells or their aggregated organic matter such as EPS or Transparent Exopolymeric Particles (TEP; Passow, 2000) or do not establish tight physical interactions and prefer to remain free‐living.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a), are known to form aggregates (Thornton 2002). For example, several species of Thalassiosira extrude long chitin fibrils, which prevent sinking and bind exopolymeric substances (EPS) also produced by the algal cells (Den et al 2023, Herth & Barthlott 1979). This creates a favorable environment for bacteria to attach, which can in turn stimulate algal EPS production (Gärdes et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Using these methods, Tran et al (2023) investigate diatom‐bacteria interactions and the diversity of glycoconjugates of Thalassiosira rotula , a widely distributed diatom in marine environments. The authors screened 78 commercially available fluorescent lectins and found six lectins that bind to glycoconjugates on T. rotula cells.…”
Section: Figurementioning
confidence: 99%